Usability study on e-Pembelajaran Sepanjang Hayat (e-PSH) at Kolej Komuniti Masjid Tanah / Siti Khairunnisa Baharudin - Baharudin, Siti Khairunnisa (2014)
Lifelong learning is the implementation of activities to improve knowledge, skills and competencies of communities. In community college, short couse is provided to support lifelong learning education. Recent statistic shows that a total of 253,016 community members had attended short courses offered by community colleges across Malaysia. Due to the response from local community, Kolej Komuniti across the country, being the organizers, need a new mechanism to facilitate the registration of participants. Therefore, e-Pembelajaran Sepanjang Hayat (e-PSH) is developed as an online application system for the short courses and is implemented at all Kolej Komuniti in Malaysia including Kolej Komuniti Masjid Tanah (KKMT). However these systems are never being measured its usability in most areas. An initial survey among the e-PSH user community, reveals that they are not very keen to use the system on a basis of user-friendliness. The system also had limited contents, that critical information such as a courses catalogue for user to choose is not readily available. Hence, this research is attempts to study the usability problem of e-PSH. Online application system for short couses at Kolej Komuniti Masjid Tanah is known as e-PSH. This study also aim to investigate the usability problems wriich are actual problem of the system implementation. Understanding the usability problems is vital to identify areas for system improvement as the administrator needed to improvise in order to increase the level of user satisfaction and provide the e-PSH system more effective. User testing with five participant had been conducted to evaluate the usability problems of the system. In order to get feedback from user, interview session had been done after user finished all the task. The result is significant for e- PSH system future improvement in- term of usability while using the online application for short course at Kolej Komuniti Masjid Tanah.